2012
DOI: 10.1111/j.1468-005x.2012.00279.x
|View full text |Cite
|
Sign up to set email alerts
|

The Internet, employment and Polish migrant workers: communication, activism and competition in the new organisational spaces

Abstract: This article discusses the content of Polish community–administered websites and trade union engagement. It is based on three sources of data, firstly, semi‐structured interviews with Polish web administrators and trade union officers in the north of England. Secondly, audits of the location of Polish administered UK websites undertaken in April 2007 and 2008. Lastly, an in‐depth thematic questionnaire was undertaken of websites in November 2008. The key findings are that the Internet is an increasingly system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 25 publications
0
35
0
Order By: Relevance
“…Is this going to turn into a union thing?'" Beyond these studies, scholars have examined other digital communication channels, like how employees communicate via websites (Fitzgerald, Hardy, and Lucio 2012), e-forums (Greene, Hogan, and Grieco 2003;Robinson 2006), employee association websites (Heckscher and Carr e 2006), union websites (Panagiotopoulos and Barnett 2015), message boards (Saundry, Stewart, and Antcliff 2012), "friending" activity (Heckscher and McCarthy 2014), and how unions use social media (Panagiotopoulos 2012). (Turkopticon is not a labor union and was not founded with formal unionization in mind.)…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Is this going to turn into a union thing?'" Beyond these studies, scholars have examined other digital communication channels, like how employees communicate via websites (Fitzgerald, Hardy, and Lucio 2012), e-forums (Greene, Hogan, and Grieco 2003;Robinson 2006), employee association websites (Heckscher and Carr e 2006), union websites (Panagiotopoulos and Barnett 2015), message boards (Saundry, Stewart, and Antcliff 2012), "friending" activity (Heckscher and McCarthy 2014), and how unions use social media (Panagiotopoulos 2012). (Turkopticon is not a labor union and was not founded with formal unionization in mind.)…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Additionally, Saundry, Stewart, and Antcliff (2012) found that workers derive social capital from digital communication with others, but labor unions had a difficult time transferring these connections into formal membership. Beyond these studies, scholars have examined other digital communication channels, like how employees communicate via websites (Fitzgerald, Hardy, and Lucio 2012), e-forums (Greene, Hogan, and Grieco 2003;Robinson 2006), employee association websites (Heckscher and Carr e 2006), union websites (Panagiotopoulos and Barnett 2015), message boards (Saundry, Stewart, and Antcliff 2012), "friending" activity (Heckscher and McCarthy 2014), and how unions use social media (Panagiotopoulos 2012). Across these studies, scholars have not found evidence that digital communication lends itself to a collective labor identity or that it improves workers' interest in joining a trade union.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Indeed, Fitzgerald et al . (: 95) note that ‘unions have advanced greatly in their ability to engage with the Internet and created centrally controlled spaces for intra‐ and extra‐union communications’. Union presence on social media can therefore present the ‘official’ view of the union, much in the same way a union's website is the ‘prominent public shop‐window of the organization’ (Bibby in Freeman, : 167).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…It serves to petrify stereotypical images of Poles in relation to employment risks and consequently contributes to their social marginalisation. This is not to deny, though, that certain segments of the Polish migrant community have been able to 'fi ght back' and resist social exclusion, which is exemplifi ed by the growing Polish migration industry [Garapich 2008], and by the proliferation of ethnic online media that provide comprehensive information on the rights of EU citizens [Fitzgerald et al 2012], not to mention the upward mobility of a signifi cant number of Polish migrants in the labour market, which clearly limits the effects of moral panic stigmatising. We must remember that Polish migrants may also act as an important resource to be used in any fi ghting back strategy, in a manner similar to that described by Van Riemsdijk [2010: 121] in her study on the 'privilege of whiteness' of Polish nurses in Norway: 'there are important differences in access to power and resources within racial and ethnic groups'.…”
Section: Resultsmentioning
confidence: 99%